Jahrbuch der berufs- und wirtschaftspädagogischen Forschung 2013 - Fasshauer, Uwe; Fürstenau, Bärbel; Wuttke, Eveline, 1960- (Schriftenreihe der Sektion Berufs- und Wirtschaftspädagogik der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE)., 2013)
Vocational education and training in Germany, especially the Dual System of Vocational Education and Training, is receiving great attention and appreciation in some EU countries, not least against the background of very high youth unemployment. In empirical analyses of the close interlocking of learning and work and in theoretical foundations of educational potential, vocational and business education research provides all actors in the vocational training system with findings, arguments and impulses for further development.